Employability of accountancy graduates of a Philippine public university - Eva Uminga Cammayo; Jeanette Ignacio Gonzales (International Journal of Evaluation and Research in Education (IJERE), 2024)
The Isabela State University aims to develop graduates equipped with skills and competence required by the industry. The graduate tracer research helps assess graduates’ employability and establish the elements that serve as a framework for enhancing students’ services and instruction. The snowball sampling was adopted and a modified questionnaire was sent via social media to Bachelor of Science in Accountancy (BSA) graduates between 2007 to 2019. There were 111 questionnaires fully accomplished received from the graduates. The results of the study show that the most significant factors contributing to employability were their educational qualifications and professional examinations. All the respondents are employed, but they found the BSA curriculum wanting in providing students with the opportunity to develop accounting skills and better prepare themselves for professional examinations. As such, the graduates recommend extending the BSA curriculum to 5 years; the on-the-job-training (OJT) program with accounting firms, and adding the required course audit. Further, to increase the graduates’ employability, the university shall provide students with the opportunity to experience the use of accounting software in actual business operations.